2022
DOI: 10.3390/su142013536
|View full text |Cite
|
Sign up to set email alerts
|

Research on Recycling Various Wastes in Papermaking as Eco-Friendly Slurry

Abstract: Waste recycling has always been a priority in the paper industry. In this study, the potential of translating various wastes in papermaking into building materials was separately evaluated. For the first time, the improvement of flexibility and sample texture after translating wastes into cementitious materials was analyzed. The results showed that 20% of the waste in alkali-activated slag slurry is the best proportion for papermaking. In addition, paper sludge and wood chips significantly improved the slurry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…It has been reported that setting times are halved when the incorporated PC is increased from 5 to 15%wt. (solution/cement = 0.6) [22].…”
Section: Criterion 2: Setting Timementioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that setting times are halved when the incorporated PC is increased from 5 to 15%wt. (solution/cement = 0.6) [22].…”
Section: Criterion 2: Setting Timementioning
confidence: 99%
“…Calcined PS has been used as a precursor in the production of geopolymers and AAC, in combination with FA [16,17], GGBFS [16], bottom ash [18] or CDW [19]. PS ash has also been used as a pozzolanic complement to PC in mortars and concrete [20][21][22]. Incorporation of PS as a source of cellulose fibers in geopolymeric FA matrices [23] made it possible to form low-density, low-shrinkage drying composites by casting [24,25].…”
Section: Introductionmentioning
confidence: 99%